Metodologías activas aplicadas por los docentes de bachillerato durante la pandemia Covid-19 en la Unidad Educativa del Milenio “Cochasquí”. - Alba, Darwin M. (2022)
The objective of this research was to determine which are the active methodologiesapplied by high school teachers of the Millennium Educational Unit ¨Cochasquí¨, given thatit was found in different bibliographic sources that teachers continue to be aligned to theuse of traditional methodologies, the which are centered on the teacher, are vertical, memorydoes not allow the development of critical, reflective, analytical thinking skills andcollaborative work. When the education curriculum is aligned with the constructivist modelthat proposes active methodological strategies focused on student teaching and learning,which allows the construction of their own knowledge from their context, taking intoaccount that the current generation is considered digital natives, their way of learning andunderstanding is different, the use of technological tools is essential in the teaching-learningprocess, this study has a mixed approach, descriptive level, type of field research. The studypopulation is finite with a total of 18 teachers, for data collection a survey was applied usingthe google FORMS tool, classroom observations were made and the microcurricular plansthat were prepared during the COVID-19 pandemic, school year 2020, were analyzed. -2021 through an observation rubric. As a result of this work, it was found that teachers applythe following active methodologies: Project-Based Learning, collaborative learning and theinverted classroom; but they apply in an inadequate way, this could be verified in classroomobservations and planning, they only propose simple activities that do not generatesignificant learning nor do they help the student to develop their potentialities for life. Forthis reason, a proposal is proposed with active methodological strategies accompanied bydifferent technological tools that teachers use to improve their teaching process.